In situ growth of Si nanowires on graphene sheets for Li-ion storage - Lu, Ziyang (2013)
Si nanowires in graphene papers were successfully prepared by supercritical fluid–liquid–solid (SFLS) process, which showed high specific capacities and charge–discharge cycling stability as anode materials for Li-ion storage. The enhancement on capacity and cycling stability of the Si/graphene composite nanostructures was attributed to the presence of graphene papers in the hybrid samples that served as a highly conductive framework and absorption of volume changes of Si nanowires during the lithiation/delithiation process. This Si/graphene electrodes maintained reversible capacities of 1400 mAh g−1 for the 30th cycle at a current density of 420 mA g−1, which is much better as compared to that of pure Si nanowires.